Fermented fish products: a review on the manufacturing process, technological aspect, sensory, nutritional qualities and metabolite profiles - Mohamed, Hajaratul Najwa; Mustafa, Shuhaimi (University College TATI, 2021)
Fermented fish products are traditional foods which have a long history of use as condiment and side dishes in many countries especially Southeast Asia and Asian countries. Today, fermented fish products are gaining importance and have a great potential in the food industry as general populace start to realize their unique characteristics. The indigenous fermented fish products are renowned for their umami taste and special aroma characters besides possess high nutritional values. This review article focuses on the manufacturing process of various fermented fish products, their technological aspect, sensory and nutritional qualities. In addition, the research works carried out on metabolites profiles of fermented fish products is also reviewed. This review paper provides an extensive knowledge and broad information on fermented fish products which can be used as reference to improve the products quality.